THE EFFECTIVENESS OF GOOGLE CLASSROOM USAGE IN THE PPISMP STUDENTS’ INTERACTION: A SURVEY - Zaharah Mohamad; Nor Azizah Atan; Badariah Mohamed; Tetep (Journal Civics And Social Studies, 2022)
This research aims to determine the effectiveness of using Google Classroom in the Malaysian Art History and Fine Arts Appreciation courses by PPISMP students. Students have used Google Classroom as an e-learning teaching and learning platform during the Movement Control Order (MCO) period due to the Covid-19 pandemic. The research design used is quantitative and qualitative using questionnaire and survey methods. The respondents were 29 PPISMP students who were taking Malaysian Art History and Fine Art Appreciation courses. From the research objectives, it is known that the majority of respondents strongly agree that lecturers always provide the latest information in e-learning using the Google Classroom platform. The majority of respondents strongly agree that the use of Google Classroom can improve students' ability to apply the knowledge and understanding gained in the Malaysian Art History and Fine Art Appreciation courses. The research results show that the types of activities that students often carry out are taking notes and delivering lecture material and submitting assignments and assignments to lecturers.